The Impact of Pro-environmental Awareness Components on Green Consumption Behavior: The Moderation Effect of Consumer Perceived Cost, Policy Incentives, and Face Culture - Shen, Minmin; Wang, Jianhua (Frontiers in Psychology, 2022)
Based on the survey data of 839 consumers in Jiangsu and Anhui provinces, this article explores the formation mechanism and internal driving force of Chinese consumers' green consumption, clarifies the effect of consumers' pro-environmental awareness components on green consumption and the moderating effect of perceived cost, policy incentives and face culture. The results of the study show that pro-environmental awareness is the basis for green consumption. However, groups with pro-environmental awareness do not choose green consumption for sure. The transform from awareness to behavior is also affected by many factors. Consumers' perceived cost is an important obstacle to green consumption, while the face culture in Chinese society has a certain role in promoting green consumption. In this study, government policy incentives have no significant direct impact and moderating effect on consumers' green consumption.